Mother's Knowledge And Education On The Motor Development Of Children Aged 3-5 Years Old In Ra Amanah Al Fatonah Desa Mengulak Kabupaten Oku Timur In 2021 - Erike Septa Prautami; Ratna Dewi (Institute of Computer Science (IOCS), 2021)
Child development is all changes that occur in children seen from various aspects, including physical (motor), language, psychosocial, socialization, moral, and belief aspects. Gross motor skills are body movements using large muscles or all limbs influenced by the child's own maturity. While fine motor is a movement that only involves certain body parts and is carried out by small muscles.This research is a quantitative study using a cross sectional approach where the independent and dependent variables are collected at the same time. The research population is all mothers who have children aged 3-5 years who attend RA. Amanah Al Fatonah, Mengulak Village, OKU Timur Regency in 2021, as many as 27 people. The sampling technique was Total Sampling technique so that the number of samples in this study was 27 respondents.The results showed that there was a relationship between knowledge and motor development of children aged 3-5 years with p value = 0.04, and there was a relationship between education and motor development of children aged 3-5 years with a p value of 0.004.Mother's knowledge and education play an important role to help optimal child development. With knowledge, mothers will obtain information, including how to properly care for children, maintain child health, and stimulate child development.